Short-term return-based contrarian profits in the international index futures markets : 1993-2002 - Neo, Janet Zhenna (2008)
In this paper, we document return reversals and investigate contrarian profits in the context of international index futures markets. Both {4,4} and {5,5} contrarian strategies account for most of the statistically significant results. These findings are robust to missing observations, seasonality, alternative profit measures, contract sizes, and exchange regulatory differences.